2017
DOI: 10.1039/c7dt02167d
|View full text |Cite
|
Sign up to set email alerts
|

Ring opening polymerisation of lactide with uranium(iv) and cerium(iv) phosphinoaryloxide complexes

Abstract: The C-symmetric uranium(iv) and cerium(iv) complexes MeSiOM(OAr), M = U (1), Ce (2), OAr = OCH-6-Bu-4-Me-2-PPh, have been prepared and the difference between these 4f and 5f congeners as initiators for the ring opening polymerisation (ROP) of l-lactide is compared. The poorly controlled reactivity of the homoleptic analogue U(OAr) (3) demonstrates the importance of the M-OSiMe initiating group. The incorporation of a nickel atom in 1 to form the U-Ni heterobimetallic complex MeSiOU(OAr)Ni (4) may be the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 19 publications
2
19
0
Order By: Relevance
“…It is earth-abundant, being more common than copper or nickel, its salts are six times less toxic than those of iron, and it is the only rare earth with a readily accessible +III/+IV redox couple. [1][2][3][4] It has been used widely as a stoichiometric oxidant in organic chemistry, as a redox active heterogeneous catalyst support, and increasingly in the development of homogeneous catalysts for a range of small molecule transformations. [1][2][3][4] The Ce III/IV redox potential can be easily tuned across an extremely large window by appropriate ligand choice, for example from E°= +1.30 V vs. Fc/Fc + for [Ce(ClO 4 ) 4 ] in 8 M HClO 4 5-8 to E pc = −2.39…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is earth-abundant, being more common than copper or nickel, its salts are six times less toxic than those of iron, and it is the only rare earth with a readily accessible +III/+IV redox couple. [1][2][3][4] It has been used widely as a stoichiometric oxidant in organic chemistry, as a redox active heterogeneous catalyst support, and increasingly in the development of homogeneous catalysts for a range of small molecule transformations. [1][2][3][4] The Ce III/IV redox potential can be easily tuned across an extremely large window by appropriate ligand choice, for example from E°= +1.30 V vs. Fc/Fc + for [Ce(ClO 4 ) 4 ] in 8 M HClO 4 5-8 to E pc = −2.39…”
Section: Introductionmentioning
confidence: 99%
“…6,20,22 We have used functionalised aryloxide ligands to support cerium(III) catalysts [Ce(L R ) 3 ] (L R = ortho-NHC-aryloxide = O(o-C 6 H 2 -t Bu 2 -2,6-CN(C 2 H 2 ) NMes)) for the formation of cyclic carbonates from CO 2 and epoxides, 23 and cerium(IV) catalysts [Me 3 SiOCe(OArP) 3 ], (OArP = ortho-phosphino-aryloxide = OC 6 H 2 -6-t Bu-4-Me-2-PPh 2 ) for the ring-opening polymerisation (ROP) of the bio-renewable ester L-lactide. 3 The development of systems that can combine two cerium cations in a molecule has received considerably less attention. However, it has been shown by EXAFS spectroscopy that the active form of the classical cerium oxidant, aqueous Ce(IV), is dinuclear, 24 so the development of robust and well-defined molecular [Ce] 2 complexes that can combine two readily accessible Ce IV states is a potentially important target for developing catalytic cerium oxidation chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…A ceric metallasilsequisiloxane derivative was generated via a tandem protonolysis oxidation reaction of [Ce{N(SiMe 3 ) 2 } 3 ] in the presence of pyridine, nicely pointing out the stabilizing influence of the dianionic silsequisiloxane ligand on the tetravalent cerium ion . More recently, the heteroleptic complexes [Ce(TriNO x )(OSiMe 3 )] and [Ce(OC 6 H 2 ‐6‐ t Bu‐4‐Me‐2‐PPh 2 ) 3 (OSiMe 3 )] were described, featuring the trimethylsiloxy ligand . Compared to alcohol proligands HOCR 3 , the respective silanols HOSiR 3 display a higher Brønsted acidity, which again is highly dependent on the substituents R and particularly pronounced in alkoxysilanols …”
Section: Introductionmentioning
confidence: 99%
“…However, we note that 5, which contains only OSiEt 3 initiating groups is a reasonable catalyst, and there is literature precedent for initiation to occur from a metal-bound OSiR 3 group (R = alkyl). 19 In general, the fastest catalyst, 2 show an experimental M n value higher than the theoretical value, for example the Cl/ODipp catalyst 3, which suggests that the initiation is less efficient and/or that only one polymer chain is initiated per catalyst molecule.…”
Section: Ring-opening Copolymerizationmentioning
confidence: 92%
“…15,16 Diaconescu's group demonstrated that cerium(IV) catalysts based on C, Chart 1 are active in lactide polymerization and our group extended this demonstration of high catalytic activity to Ce IV -phosphinoaryloxide complexes (D, Chart 1) in a recent report. 10,[17][18][19] Some of the key catalyst features in lactone ROP, namely the Lewis acidity of the metal and the nature of the metal-oxygen bond, are also of key importance for the ring-opening copolymerization (ROCOP) of epoxides with CO 2 or anhydrides. [20][21][22] In epoxide/CO 2 and epoxide/anhydride ROCOP, dinuclear catalysts generally show improved activities compared to mononuclear analogues when metal cooperativity is possible, and dinuclear pathways are proposed to facilitate epoxide activation and ring-opening.…”
Section: Introductionmentioning
confidence: 99%